Primary retroperitoneal extraovarian granulosa cell tumor - Sharma, Pragya; Singh, Vikram; Mishra, Niharika; Gopinath, Manoj; Gupta, Prashant (Autopsy and Case Reports, 2022)
Extraovarian granulosa cell tumors (GCTs) develop from ectopic gonadal tissue situated along the embryonal route of the genital ridge. Primary retroperitoneal tumors are extremely rare, with an incidence of 02% -06% and 80-85% probability of malignancy. Only eight such case reports have been published previously. We herein, report a rare case of extraovarian retroperitoneal GCT in a 55-year-old woman who presented with intermittent left lumbar region pain of one-year duration. She had a history of hysterectomy and bilateral salpingo-oophorectomy 8 years ago for uterine leiomyoma. Laparotomy revealed a retroperitoneal mass measuring 8cm x 10cm x 20cm in size, solid cystic with areas of necrosis and hemorrhage. The gross features, classical histopathology, and positive immunostaining of the retroperitoneal mass with inhibin, calretinin, PR, WT1 and immunonegativity for EMA were characteristic of adult-type GCT. Excluding any previous history of primary ovarian GCT in this patient, a de-novo retroperitoneal diagnosis was established.